Molecular Study of Hepcidin HAMP (-582A/G) Gene Polymorphisms and Measurement of Serum Hepcidin Level among Sudanese Patients with Anemia of Chronic Kidney Disease - Hussen Abdelrhman, Amged; Mohammed Khalid, Khalid; Abdelrhman Abdelgadir, Enaam (Journal of DNA And RNA Research, 2020)
Background Anemia of chronic disease is anemia found in certain chronic disease states, is typically marked by the disturbance of iron homeostasis or hypoferremia. Chronic renal failure is currently known as Chronic Kidney Disease (CKD) or Chronic Renal Insufficiency (CRI) implies long-standing, progressive and irreversible renal parenchyma disease resulting in diminished renal function up to 40 to 60%. Often, chronic kidney disease is diagnosed as a result of screening of people known to be at risk of kidney problems, such as those with high blood pressure or diabetes and those with a blood relative with chronic kidney disease. This disease may also be identified when it leads to one of its recognized complications such as cardiovascular disease, anemia, or pericarditis.                             Methods Sysmex kx21 used to CBC and the Cobase411 used to iron profile. Enzyme-Linked immunoassay (ELISA) was used to determine the level of serum hepcidin.  Sample preparation and PCR detection of HAMP DNA Polymorphisms: Restriction digestion of PCR products was done using Fast Digest. (Figure 1).                                                                                         Results Serum hepcidin levels higher in patients with anemia of chronic kidney disease compared with healthy controls mean. The polymorphisms of the hepcidin gene promoter in Sudanese patients with ACKD showed that the hepcidin HAMP AA genotype 70, AG 23, and GG 7 in 100 patients dialysis-dependent and AA 83, AG 17 and GG 0, and the allele A are more frequent in patients affected by ACKD. Significant statistical association observed between the hepcidin level and end-stage kidney disease. Conclusion This study evaluates for the first time the association between anemia of chronic kidney disease and hepcidin genes promoter polymorphisms and show that the hepcidin HAMP AA genotype and the allele A are more frequent in patients affected by ACKD, further investigation is needed, our data support the hypothesis and hepcidin HAMP are important in the pathophysiology of ACKD.
Keywords: Anemia; Hepcidin HAMP gene polymorphism; Chronic kidney disease patients